Redox Signaling and CBF-Responsive Pathway Are Involved in Salicylic Acid-Improved Photosynthesis and Growth under Chilling Stress in Watermelon - Cheng, Fei; Lu, Junyang; Gao, Min; Shi, Kai; Kong, Qiusheng; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2016)
Salicylic acid (SA) plays an important role in plant response to abiotic stresses. This study investigated the potential role of SA in alleviating the adverse effects of chilling stress on photosynthesis and growth in watermelon (Citrullus lanatus). Chilling stress induced the simultaneous accumulation of free and conjugated SA in watermelon plants, and the chilling-induced SA production was attributed to the phenylalanine ammonia-lyase pathway. Applying SA at moderate concentrations induced chilling tolerance, whereas inhibition of SA biosynthesis by L-α-aminooxy-β-phenylpropionic acid (AOPP) increased the photooxidation of PS II under chilling stress in watermelon, resulting in reduced photosynthesis and growth. Chilling induced a transient increase in the ratios of reduced to oxidized glutathione and reduced ascorbate to dehydroascorbate. Then, the expression of antioxidant genes was upregulated, and the activities of antioxidant enzymes were enhanced. Furthermore, SA-induced chilling tolerance was associated with cellular glutathione and ascorbate homeostasis, which served as redox signals to regulate antioxidant metabolism under chilling stress. AOPP treatment stimulated the chilling-induced expression of cold-responsive genes, particularly via C-repeat binding factors CBF3 and CBF4. These results confirm the synergistic role of SA signaling and the CBF-dependent responsive pathway during chilling stress in watermelon.